Streamlining the Internet-fiber connection. - Dixit, S.
Discusses the evolution towards WDM optical fiber networks for the development of the Internet. The topics of multiprotocol label switching and multiprotocol lambda switching, together with the client server model, the big fat router model, the peer-peer model and the augmented model are considered. The authors also focus on routing and survivability aspects
Keywords: Internet; WDM optical fiber networks; Augmented model; Big fat router model; Client server model; Multiprotocol label switching; Multiprotocol lambda switching; Peer-peer model; Routing; Survivability